Sąd konstytucyjny jako „sąd ustanowiony ustawą” : Rozważania na tle wyroku Europejskiego Trybunału Praw Człowieka z dnia 7 maja 2021 roku Xero Flor przeciwko Polsce - Kubik, Jerzy (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
The article concerns the issue of a constitutional court as a tribunal established by law according to the European Convention on Human Rights. The considerations are based on the ruling of the European Court of Human Rights from 7th May 2021 in Xero Flor vs. Poland case (application no. 4907/18). The applicant company demanded to recognize that its right to a fair civil trial was breached. The root cause for that was a discontinuation of proceedings based on a constitutional complaint submitted by a court, one member of which was elected as a judge in a faulty procedure. The Court made an interpretation of the notions of a “tribunal” (which also means constitutional court) and “tribunal established by law”, which are contained in Article 6 § 1 of the European Convention on Human Rights. The author agreed with the conclusions of the Court and presented arguments for such an understanding of these notions.
Keywords: constitutional court; tribunal established by law; Constitutional Court; Convention